Postharvest stress manipulation in Tenderstem® broccoli – examining the potential for stress-adaptative responses to promote sustainable quality retention - Gage, Ewan; Terry, Leon A.; Falagán, Natalia (Taylor & Francis, 2025)
Low temperature postharvest management is used to reduce quality and nutritive losses in broccoli after harvest, although this increases postharvest energy demand and the environmental impacts of food supply chain. Hydrogen peroxide (H2O2) and methyl jasmonate (MeJA) have been shown to reduce postharvest yellowing in broccoli by enhancing oxidative stress resistance and were examined as treatments for Tenderstem® broccoli florets to offset the effects of warmer storage temperatures. H2O2 elicitation was perceived on a regulatory level through activation of the jasmonate pathway, but did not reduce postharvest yellowing. MeJA treatment was detrimental to quality, even at concentrations shown to be beneficial for conventional broccoli varieties. Carotenoid accumulation was shown to be a leading factor in Tenderstem® yellowing during early storage, while photopigment degradation contributed to late stage quality loss. The physiological basis for floret yellowing in Tenderstem® was also shown to be due to carotenoid accumulation rather than chlorophyll loss. These results highlight the impact of genotypic and developmental effects on stress perception and response, which hinder optimisation of hormesis-based approaches for postharvest management.
Keywords: Hydrogen peroxide; methyl jasmonate; temperature; OPR3; pheophytinase; 30 Agricultural, Veterinary and Food Sciences; Biotechnology; 3001 Agricultural biotechnology; 3008 Horticultural production; 3108 Plant biology